PENGARUH PELAYANAN,HARGA,DAN LOKASI TERHADAP KEPUASAN PELANGGAN BENGKEL HYUNDAI KALIMALANG - Ali Sujana; Irvan F.C. Oentoeng (STIE Tri Bhakti, 2019)
Influence, Price, and Location on Customer Satisfaction Hyundai Kalimalang Workshop.This study aims to examine the effect of service, price, and location both partially and simultaneously to customer satisfaction.This research PT. Hyundai Mobil Indonesia Kalimalang. The population in this study is the customer workshop PT. Hyundai Mobil Indonesia Kalimalang, while the total sample used in this study were 120 respondents.Based on the result of data analysis and discussion can be concluded that : 1) service have a positive and significant effectto customer satisfaction, with service regression coefficient value (XI) equal to 0,120 and significant value equal to 0,021.2) the price has a positive and significant effect on customer satisfaction, with a price regression coefficient value (X2) of 0.356 and a significant value of 0.0003) location has the positive and significant effect on customer satisfaction, with the value of the regression coefficient of location (X3) equal to 0,318 and significant value equal to 0,000.4) price and location services simultaneously have a positive and significant effect on customer satisfaction with an F value of 49.215 and a significance value of 0.000.